Impacto de los fertilizantes Nitrogenados de lenta liberación en la productividad agrícola. - Tello Arreaga, Yoel Jonathan (2024)
In the development of this research based on the "Impact of slow-release nitrogen fertilizers on agricultural productivity." in which it was proposed as an objective to establish the impacts of the main slow-release nitrogen fertilizers on agricultural productivity. The methodology is determined to be based on a type of explanatory research, where it was developed under a descriptive-analytical approach, with a qualitative research design, in its development, topics such as the definition of nitrogen fertilizers, their classification, which are coated or encapsulated fertilizers, the main slow-release nitrogen fertilizers used in agriculture, the effects of slow-release nitrogen fertilizers on agricultural yield and its economic impact compared to commercial fertilizers were taken into account. As for the results, they demonstrate that the main slow-release nitrogen fertilizers used in agriculture include coated urea, coated nitrogen sulphate and coated ammonium nitrate and that these have a higher initial cost, but their efficient use and long-term benefits can justify the investment, operating costs are reduced by reducing the amount of fertilizer needed, the frequency of application and crop yield. In conclusion, they have a control offer many significant benefits in crop yield, reducing the risk of environmental contamination by optimizing plant growth and development and the cost-effectiveness ratio of slow-release fertilizers has its long-term benefits justifying its initial investment due to the high value.